The burden of depression and malnutrition in the elderly population of western Rajasthan - Shikha Upadhyay; Neha Mantri; Akhil Dhanesh Goel; Nitin Kumar Joshi; Nitesh Kumar; Pankaj Bhardwaj; Kuldeep Singh (International Journal of Public Health Science (IJPHS), 2022)
Background: With changing demography, developing countries will be outnumbered by the elderly and their associated chronic diseases. The geriatric population is at increased risk of malnutrition with multifactorial factors, especially Depression. The current study aims to explore potential linkages between malnutrition and depression in the geriatric population.Method: A cross-sectional study was planned at Tertiary healthcare facilities at Jodhpur, Western Rajasthan, India from April to June 2018. After consent from 310 elderly patients attending OPD, a pre-tested questionnaire was directed to record socio-demographic data. Assessment of Malnutrition status using Mini Nutritional Assessment, Depression using Geriatric Depression Scale, Physical frailty using Activities of Daily Living and Instrumental Activities of Daily Living was done. Chi-square, Fischer test, and Mann-Whitney U test was used to compare nominal data as counts and percentage. The mean and standard deviation were used to characterize continuous data. Multiple logistic regression was used to compute the corrected ODDs ratio. Significant was defined as a p-value of less than 0.05.Results: Out of 310 elderly, 192 (61.9%) participants on the MNA scale were categorized as having poor nutrition and 99 (31.9%) were suffering from depression. The elderly at risk of malnutrition among depressed was 75.8 % (n=99) with preponderance for females, and minor disabilities. Multivariate analysis suggested an association of lower socioeconomic status and rural residence in the elderly.Conclusion: Nutritional deficit and depression are interrelated. Depression and malnutrition are linked in a destructive cycle but the causality remains elusive. This synergy could be detrimental to survival.Keywords: Malnutrition, Depression, Aged, Geriatric, Elderly, Frailty, Nutrition Disorders, Chronic disease, Tertiary healthcare, India.